2021
DOI: 10.3390/jcm10235664
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes between Minimally Invasive Lateral Approach Vertebral Reconstruction Using a Rectangular Footplate Cage and Conventional Procedure Using a Cylindrical Footplate Cage for Osteoporotic Vertebral Fracture

Abstract: The aim of the current study was to compare outcomes between lateral access vertebral reconstruction (LAVR) using a rectangular footplate cage and the conventional procedure using a cylindrical footplate cage in patients with osteoporotic vertebral fracture (OVF). We included 46 patients who underwent anterior–posterior combined surgery for OVF: 24 patients underwent LAVR (Group L) and 22 underwent the conventional procedure (Group C). Preoperative, postoperative, and 1- and 2-year follow-up X-ray images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…If treating patients with osteoporosis using the corpectomy/expandable cage strategy, which allows for distraction to achieve correction of local kyphosis caused by the fracture, the surgeon may use supplemental PS fixation at the segments longer than 1 level above and below the fracture, even with a wide-footprint, expandable corpectomy cage. 11,12 The CT scans also revealed a progressive decrease in spinal canal compromise due to retropulsed vertebral body fragments, averaging 33.4% preoperatively, 28.9% postoperatively, and 23.1% at the latest evaluation. However, it remains unknown to what degree of severity in osseous retropulsion this strategy can continue to be effective.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…If treating patients with osteoporosis using the corpectomy/expandable cage strategy, which allows for distraction to achieve correction of local kyphosis caused by the fracture, the surgeon may use supplemental PS fixation at the segments longer than 1 level above and below the fracture, even with a wide-footprint, expandable corpectomy cage. 11,12 The CT scans also revealed a progressive decrease in spinal canal compromise due to retropulsed vertebral body fragments, averaging 33.4% preoperatively, 28.9% postoperatively, and 23.1% at the latest evaluation. However, it remains unknown to what degree of severity in osseous retropulsion this strategy can continue to be effective.…”
Section: Discussionmentioning
confidence: 95%
“…2,7 To address this biomechanical need by using the minimally invasive surgery (MIS) techniques, several recent reports introduced corpectomy of the fractured vertebra, followed by expandable cage reconstruction via a mini-open, direct lateral approach on traumatic as well as osteoporotic burst fractures. [8][9][10][11][12][13][14][15][16] However, a negative aspect of this corpectomy/expandable cage strategy is that the corpectomy not only needs meticulous management of the segmental vessels overlying the fractured vertebral body, but also involves the technical challenge of removing the retropulsed fragments while controlling epidural bleeding. 8,9,[12][13][14][15] In addition, an expandable cage placed for reconstructing the corpectomy defect is subjected to a greater stress concentration as compared with a single-level cage at the interface between the cage footplate and the vertebral endplate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our research is consistent with previous studies regarding quality-of-life evaluations. In 2016, Theologis et al conducted a case-control study which revealed that patients with unstable lumbar burst fractures, who underwent corpectomy and anterior column reconstruction via a mini-open, extreme lateral, transpsoas approach with short-segment posterior xation, and were evaluated with the SF-12, had a physical health score of 42% and a mental health score of 50% [19]. Our results, on the other hand, demonstrate an even better quality-of-life, with an average physical health score of 55% and a mental health score of 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Naoki Segi et al [ 3 ] retrospectively compared outcomes between MIS via an anterolateral approach (LAVR) using a rectangular footplate cage for vertebral reconstruction (Group L) and the conventional open anteroposterior surgery (group C) with a cylindrical footplate cage in patients aged >56 years suffering from osteoporotic fractures, neurological deficit, severe lower back pain, and pseudarthrosis. The authors showed that the rectangular footplate cage offers superior mechanical support that is derived from the footplate, while the rate of bony fusion was higher than in Group C. The authors underlined the differences that were found both in the fusion rate and fusion morphology.…”
mentioning
confidence: 99%